Determinants of the public acceptance of the elite sport policy in Japan - Funahashi, H.; Mano, Y. (Sport Science Research, 2014)
Public investment for elite sport is generally justified on the basis that the elite sport success has a wide range of social and psychological benefits for the public (Grix & Carmichael, 2011; Goodwin & Grix, 2011). Governments increasingly use this argument to further invest in elite sport and participate in the `global sporting arms race (Oakley & Green, 2001)` without showing any evidence to convince the taxpayers, despite the recognition of the necessity to obtain understanding of the whole society (Ministry of Education, Culture, Sports, Sciences & Technology in Japan [MEXT], 2012). Therefore, the purpose of this study was to examine the determinants that influence public acceptance of the development of the elite sport policy in Japan. Data was collected from n=1,000 stratified randomly selected Japanese by means of an Internet survey. The results of this empirical study reveal that the public acceptance of the promotion of elite sport policy is determined by their perceived benefits of elite sport policy which produces the success of Japanese athletes, and perceived risks, namely negative perspective of elite sport. The public`s perceived benefits and risks of elite sport are further determined by social trust in the elite sport actors and the Japanese athlete`s role model influence, except the influence of social trust on risk perception.